Influence of bionic footwear on lower limb biomechanics across running experience levels: a controlled laboratory study - Li, Xue; Shao, Enze; Fang, Yufei; Wang, Dongxu; Zheng, Zhiyi; Chen, Hairong; Liu, Qian; Fekete, Gusztáv; Sun, Dong; Gu, Yaodong (Frontiers in Sports and Active Living, 2025)
IntroductionWhile the biomechanics of lower extremity during running and the impact of conventional running shoes on these traits have been extensively investigated, the influence of bionic shoes on runners remains largely, especially those runners with different experience levels. The aim of this study was to evaluate the biomechanical differences between experienced and novice runners when wearing two distinct types of footwear: bionic shoes and neutral shoes.MethodsFourteen healthy male heel-strike runners participated and completed the running test wearing two pairs of running shoes respectively. A two-way-repeated-measures analysis of variance was used to determine the effects of participant experience level and shoe type on joint biomechanics. During the stance phase, shoe design primarily influenced the kinematic and dynamic performance of the ankles, knees, and hip joints.ResultsWhen participants wore bionic shoes, there was a significant increase in the range of motion of the ankle and hip joints (p < 0.010), a remarkable increase in knee joint angular velocity (p < 0.010), and a significant decrease in hip joint angular velocity (p < 0.001). Concerning differences in experience levels, experienced runners exhibited significantly higher ankle joint angular velocity (p = 0.005) and knee joint angular velocity (p < 0.010) compared to novice runners, whereas novice runners demonstrated a significantly greater range of knee joint motion than experienced runners (p < 0.050).ConclusionOur findings preliminarily suggest that experienced runners demonstrate superior performance as well as better stability and motor control of knee joint compared to novice runners who showed smaller knee angular velocity and greater range of motion during running. Furthermore, the increased range of motion of the ankle and hip joints in bionic shoes can activate the relevant muscle groups to a greater extent, which have a certain potential effect on the training performance of runners and the improvement of muscle control ability. While, due to the lack of a certain movement foundation, novice runners may have higher risk of injury.